Association between race/ethnicity and neuroimaging biomarkers in middle‐ and older‐aged adults: Neuroimaging: Sex and ethnoracial differences – biomarkers. (7th December 2020) - Turney, Indira C; Lao, Patrick J; Rentería, Miguel Arce; Laing, Krystal K; Beato, Juliet M; Chesebro, Anthony G; Amarante, Erica; Igwe, Kay C; Schupf, Nicole; Mayeux, Richard; Manly, Jennifer J; Brickman, Adam M
Abstract: Background: Alzheimer's disease and related disorders (ADRD) disproportionately affect African American, Hispanic, and American Indian older adults. Previous studies report racial/ethnic differences in markers of aging and neurodegeneration, but results are inconsistent due to small, non‐representative samples. We hypothesized that accelerated aging would manifest as a stronger negative relationship between age and MRI biomarkers among community‐dwelling racial/ethnic minorities compared with non‐Hispanic Whites. Method: ADRD‐related neuroimaging measures of composite cortical thickness (CT) in AD signature regions and white matter hyperintensity (WMH) volume were assessed in White (n=274), Black (n=451), and Hispanic (n=663) participants from community‐based, intergenerational studies of cognitive aging and dementia. WHICAP participants are Medicare‐eligible participants aged 65 and older. The Offspring cohort includes middle‐aged children of the WHICAP study participants (of the 1482 participants, 1209 families were represented). We examined the association of cohort age and race/ethnicity with each imaging marker, after adjusting for sex/gender and family relatedness, and tested interactions between cohort age and race/ethnicity in separate models. Result: WHICAP participants were 75±6.5 years old and Offspring participants were 55±10.5 years old at time of MRI. As expected, WHICAP participants had lower CT in AD signature regions than Offspring (β=‐.06, 95%CI:‐.05, ‐.08). Compared with Whites, Blacks and Hispanics had lower CT in AD signature regions, but an interaction between cohort age and race/ethnicity revealed that older Blacks had disproportionately thinner CT in AD signature regions (β=‐.05, 95%CI:‐.01, ‐.10). Offspring participants had lower WMH volume than WHICAP participants (β=‐1.4, 95%CI:‐2.1, ‐.58). Blacks had more WMH burden overall (β=1.04, 95%CI:.13, 2.0), but there were no interactions between race/ethnicity and cohort age on WMH burden. Conclusion: Among diverse, community‐based participants, there are disparities in markers of brain atrophy in both cohorts but this effect is intensified with age, where older Blacks show disproportionately greater brain atrophy compared with other groups. Disparities in small vessel cerebrovascular disease are apparent in middle‐age and late‐life, but this effect is similar across age‐groups. Results suggest that racial/ethnic disparities in markers of brain aging and disease are apparent even in middle‐age and, in the case of neurodegeneration, may amplify with increasing age. These differences may be due to accelerated aging secondary to sociocultural factors and experiences.